Contribution of activity-based steering tools in the management of economic business performance - Moahmed azzedine NAMOUN; Bilal GUENDOUZ (Journal of Excellence for Economics and Management Research, 2020)
This article aims to study activity-based management methods, namely (1) activity-based costs (2) activity-based budgets (3) activity-based management and their contribution to management of company performance.        At the end of this study, we concluded that the activity-based management tools participate in the performance management of the economic enterprise through the analysis of the activities and their participation in the creation of value, in Indeed, the company tries to strengthen the activities creating value, on the other hand, it aims to control the activities which do not create value in order to minimize its costs.       As a recommendation, we propose the adoption of activity-based management tools within the economic enterprise and the training of the staff of the accounting function to master these tools.